Effects of Tamoxifen on L-Glutamate Transporters of Astrocytes - Kaoru Sato; Yoshihiko Saito; Jun-ichiro Oka; Tomohiko Ohwada; Ken Nakazawa (Elsevier, 2008)
Tamoxifen (Tam) decreased the clearance of L-glutamate (L-Glu) by cultured astrocytes at 1 pM, 1 nM, and 1 μM, but became toxic at 10 μM. When L-Glu transporters were mostly inhibited by threo-β-benzyloxyaspartate (TBOA) (1 mM) or D,L-threo-β-hydroxyaspartate (THA) (1 mM), Tam (1 nM) did not change extracellular L-Glu concentration, confirming that Tam attenuates L-Glu transport through L-Glu transporters. ICI182,780, LY294002, and U0126 inhibited the effect of Tam dose-dependently, suggesting the involvement of estrogen receptors (ERs), the phosphatidylinositol 3-kinase (PI3K) cascade, and the mitogen-activated protein kinase (MAPK) cascade in the effect of Tam. Keywords:: tamoxifen, L-glutamate transporter, astrocyte